2022
DOI: 10.1371/journal.pone.0268648
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal mortality and associated factors among neonates admitted to neonatal intensive care unit at public hospitals of Somali Regional State, Eastern Ethiopia: A multicenter retrospective analysis

Abstract: Background Neonatal mortality remains a public health problem in the developing world. Globally, around 2.5 million neonatal deaths are reported annually with the highest mortality concentrated in sub-Saharan Africa and South Asia. In comparison with countries demonstrating the lowest neonatal mortality, the risk of mortality is over 30 times higher in sub-Saharan Africa. Ethiopia is among the countries with a high neonatal mortality rate, and the burden of this mortality remains unreported in many pastoralist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
5
4
1
Order By: Relevance
“…Our study revealed a signi cant nding: approximately half of the neonates from in-vitro fertilization (IVF) pregnancies succumbed to NRDS. This aligns with previous research indicating a higher incidence of LBW and preterm births in IVF pregnancies 25 , suggesting that IVF could signi cantly amplify the risk of neonatal mortality from NRDS. It is well known that lack of antenatal care during pregnancy signi cantly escalates the risk of delivery complications, endangering the fetus 25 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study revealed a signi cant nding: approximately half of the neonates from in-vitro fertilization (IVF) pregnancies succumbed to NRDS. This aligns with previous research indicating a higher incidence of LBW and preterm births in IVF pregnancies 25 , suggesting that IVF could signi cantly amplify the risk of neonatal mortality from NRDS. It is well known that lack of antenatal care during pregnancy signi cantly escalates the risk of delivery complications, endangering the fetus 25 .…”
Section: Discussionsupporting
confidence: 91%
“…This aligns with previous research indicating a higher incidence of LBW and preterm births in IVF pregnancies 25 , suggesting that IVF could signi cantly amplify the risk of neonatal mortality from NRDS. It is well known that lack of antenatal care during pregnancy signi cantly escalates the risk of delivery complications, endangering the fetus 25 . Regular antenatal care and examination are crucial for ensuring perinatal health, especially in developing countries 26 .…”
Section: Discussionsupporting
confidence: 91%
“…This finding indicates a significant number of newborns admitted to the NICU experienced mortality. The results of our analysis show some similarity to previous studies conducted in different regions of Ethiopia, such as northwestern Ethiopia (151 per 1000 live births), Gondar University Comprehensive Specialized Hospital (173 per 1000 live births), Somali Regional State Ethiopia (186 deaths per 1000 live births), and Wollega (183.4 per 1000 live births) (10,23,38,39). However, our findings are higher than the mortality rates reported in studies conducted at Felege Hiwot referral hospital, Bahir Dar (25) and Jimma University medical center (33).…”
Section: Discussionsupporting
confidence: 86%
“…As comparison, a child born from this region has a probability of eleven times more likely to die in the first month of life than a child born in a high-income countries (6). Similar studies have also shown that the risk of neonatal mortality is beyond 30 times higher in Sub-Saharan Africa than in the lowest mortality country (10). Neonatal mortality rates also significantly vary among the countries and regions with a huge toll of deaths attributed to the low-income countries (11).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation